2020
DOI: 10.1016/j.clinthera.2019.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Health Care Cost in Patients With Schizophrenia Treated With Brexpiprazole Versus Other Oral Atypical Antipsychotic Therapy

Abstract: Purpose: Brexpiprazole is an oral atypical antipsychotic (OAA) for the treatment of schizophrenia (SCZ). This study compared all-cause and psychiatric inpatient hospitalization and medical costs in adult patients with SCZ newly treated with brexpiprazole versus other US Food and Drug Administratione approved OAAs in a real-world setting.Methods: This retrospective cohort study analyzed data from: (1) the IBM MarketScan Commercial and Medicare Supplemental databases, and the MarketScan Multi-State Medicaid data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…Finally, when brexpiprazole treatment was examined compared to other SGAs, it was found to be associated with fewer psychiatric hospitalizations per year than paliperidone and quetiapine. No significant differences in other efficacy measures emerged between patients treated with brexpiprazole and those with other SGAs [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, when brexpiprazole treatment was examined compared to other SGAs, it was found to be associated with fewer psychiatric hospitalizations per year than paliperidone and quetiapine. No significant differences in other efficacy measures emerged between patients treated with brexpiprazole and those with other SGAs [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, patients treated with lurasidone displayed greater adherence when compared to patients treated with other SGAs [ 60 ]. Furthermore, one study analyzed the efficacy of brexpiprazole, and no significant differences emerged when treated patients were compared with those treated with other SGAs [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“… Previous high-dose antipsychotic therapy (Chlorpromazine-equivalent doses >800 mg) is an independent risk factor for brexpiprazole discontinuation in patients with schizophrenia or schizoaffective disorder. Yan et al 29 ≥ 52 Follow-up Schizophrenia 6254 176 Ziprasidone (391) Paliperidone (453) Lurasidone (523) Aripiprazole (786) Quetiapine (1234) Olanzapine (1264) Retrospective cohort study. Brexpiprazole users had the lowest mean psychiatric costs among all oral atypical antipsychotic users ($12,013).…”
Section: Efficacy and Safetymentioning
confidence: 99%
“…Yan et al 29 conducted a retrospective, real-world cohort study to compare all-cause and psychiatric hospitalization and medical costs in patients newly treated with brexpiprazole versus other atypical antipsychotics by drawing on the available US insurance claims data. This study has demonstrated that all-cause total costs and all-cause medical costs did not differ across atypical antipsychotic groups; however, patients treated with brexpiprazole had the lowest mean psychiatric costs of all patients prescribed atypical antipsychotics ( Table 2 ).…”
Section: Summary Of Other Studies Of Interestmentioning
confidence: 99%
See 1 more Smart Citation